LEARNING CYCLE 9E DAN SELF CONFIDENCE: DAMPAK KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Gusti Rahmadi; Siska Andriani; Iip Sugiharta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze the influence of the Learning Cycle 9E instructional model on students abilities in solving mathematical problems, to assess the impact of varying levels of self-confidence (high, medium, low) on these abilities, and to explore the interaction effect between the Learning Cycle 9E model and self confidence on students mathematical problem solving skills. This study employed a quasi experimental design. The population comprised eighth-grade students at MTs Negeri 1 Bandar Lampung. Cluster random sampling was applied as the sampling method. Data collection involved administering a mathematical problem-solving test and a self-confidence questionnaire. Hypothesis testing was conducted using two-way ANOVA. The findings of the study indicate that (1) the Learning Cycle 9E instructional model significantly influences students’ mathematical problem-solving abilities; (2) different levels of self-confidence (high, medium, low) affect students’ skills in solving mathematical problems; and (3) there is a significant interaction between the Learning Cycle 9E model and self-confidence in shaping students’ mathematical problem-solving performance.